THE ROLE OF INNOVATIVE LEADERSHIP IN DEVELOPING ORGANIZATIONAL CREATIVITY AMONG SPORTS DIRECTORS AND SCHOOL ACTIVITIES IN IRAQ - Salim Khalaf Fahad; Khalid Mahmood Raoof; Khalid Mahmood Raoof; Ahmed Najm Abdullah (Proximus Journal Publishing, 2024)
This study aimed to identify the levels of innovative leadership and organizational creativity, as well as determining the relationship between innovative leadership and organizational creativity among sports directors in the general directorates of education (GDE) in Iraq from the point of view of its employees. The researchers hypothesized that there is a statistically significant correlation between innovative leadership and organizational creativity. The researchers used the descriptive approach with the correlational coefficient. It adopted and the scales of innovative leadership and organizational creativity on a 425 employees and supervisors, chosen purposefully. The study reported that directors sports and school activities in the Iraqi governorates have an acceptable level of innovative leadership and possess organizational creativity at an average level. Findings also showed the presence of a direct relationship between innovative leadership and organizational creativity for directors of sports and school activities in the GDE in the Iraqi governorates . Therefore, it is recommended that holding workshops and special developmental courses for the development of leadership and innovative qualities and other leadership and personal characteristics, as well as organizational creative skills for managers of sports activities in the GDE in the Iraqi governorates
Keywords: Activities; innovative leadership; organizational creativity